Cyprus : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Cyprus. (IMF Staff Country Reports; Country Report ;, 2018)
Cyprus is recovering strongly from the 2012-13 crisis. GDP growth is projected to remain above 4 percent in 2018-19, buoyed by services and foreign-financed construction. Unemployment is rapidly declining while large fiscal primary surpluses are putting public debt back on a declining path. Nevertheless, crisis legacies continue to weigh on the banking system. In early 2018, difficulties in the Cyprus Cooperative Bank led the authorities to intervene, albeit at a significant fiscal cost. In the process, a package of legislative measures strengthening the insolvency and foreclosure regime was also approved, which is now catalyzing the cleanup of bank balance sheets. These developments have led to a sovereign ratings upgrade, restoring Cyprus's investment grade status.